THE THEORY OF AGRICULTURAL LAW’S LEGAL NATURE - Bezzubov, Dmytro; Korneev, Yurii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The system of law is an internal structure of law objectively predetermined by the system of social relationships and which comprises interdependent norms that are logically divided into fields, subfields and institutes. A subject matter of legal regulation is usually seen as a defining criterion for a system of law. It is the main objective basis for division of legal norms in legal fields. It is supplemented by the method of legal regulation.